2000
DOI: 10.1128/jvi.74.8.3537-3542.2000
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Recombination of Live, Attenuated Immunodeficiency Virus Vaccine with Challenge Virus to a More Virulent Strain

Abstract: Live, attenuated immunodeficiency virus vaccines, such as nef deletion mutants, are the most effective vaccines tested in the simian immunodeficiency virus (SIV) macaque model. In two independent studies designed to determine the breadth of protection induced by live, attenuated SIV vaccines, we noticed that three of the vaccinated macaques developed higher set point viral load levels than unvaccinated control monkeys. Two of these vaccinated monkeys developed AIDS, while the control monkeys infected in parall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 30 publications
(13 reference statements)
1
40
1
Order By: Relevance
“…However, evidence of a clear attenuation threshold in SIV-vaccination studies suggests the existence of a direct relationship between replication competence and degree of protection conferred. If the efficacy of vaccination depends on the replication competence of the virus, the success of further attenuation strategies might be limited (9,17,35). Furthermore, reversion to a pathogenic phenotype poses serious concerns about the application of such attenuated virus vaccines to human disease (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, evidence of a clear attenuation threshold in SIV-vaccination studies suggests the existence of a direct relationship between replication competence and degree of protection conferred. If the efficacy of vaccination depends on the replication competence of the virus, the success of further attenuation strategies might be limited (9,17,35). Furthermore, reversion to a pathogenic phenotype poses serious concerns about the application of such attenuated virus vaccines to human disease (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Most attempts to develop such a vaccine have focused on the experimental model system of the pathogenic simian immunodeficiency virus (SIV) infection of macaques (8,9,(12)(13)(14)(15), and these attenuated vaccines appear to be promising candidates for future applications to HIV infection. Nonetheless, the possibility that a live-attenuated virus reverts to a pathogenic form has been substantiated extensively (16)(17)(18) and may pose serious limitations to any future experimentation in humans.…”
mentioning
confidence: 99%
“…The only vaccine that has consistently provided sterilizing immunity against FV is a live attenuated virus (3,4). Unfortunately, live attenuated retroviruses have the potential to mutate and recombine into virulent forms, making them unsafe for use in humans (5)(6)(7)(8). Nevertheless, attenuated viruses are powerful tools for studying the basic requirements for vaccine protection.…”
mentioning
confidence: 99%
“…Studies in primate models have demonstrated that attenuated viruses have the potential to revert to pathogenic variants and cause disease. 65 However, a safe potential mechanism to mimic the persistence of an immunogen in a vaccinated individual would be to induce anti-idiotypic Abs mediating stimulatory interactions with vaccine-induced idiotypic anti-HIV Abs to sustain their presence. Previous research has demonstrated that vaccine-induced anti-HIV Abs display the 1F7 idiotype.…”
Section: Utilizing Idiotypic Repertoire Freeze To Maintain Vaccine Inmentioning
confidence: 99%